CsMYB Transcription Factors Participate in Jasmonic Acid Signal Transduction in Response to Cold Stress in Tea Plant (Camellia sinensis) - Zhaolan Han; Chen Zhang; Huan Zhang; Yu Duan; Zhongwei Zou; Lin Zhou; Xujun Zhu; Wanping Fang; Yuanchun Ma (Plants, 2022)
Low-temperature stress is an increasing problem for the cultivation of tea (Camellia sinensis), with adverse effects on plant growth and development and subsequent negative impacts on the tea industry. Methyl jasmonate (MeJA), as a plant inducer, can improve the cold-stress tolerance in tea plants. R2R3-MYB transcription factors (TFs) are considered potentially important regulators in the resistance to cold stress in plants. However, the molecular mechanisms, by which MYB TFs via the jasmonic acid pathway respond to cold stress in the tea plant, remain unknown. In this study, physiological and biochemical assays showed that exogenous MeJA application could effectively promote ROS scavenging in the tea plant under cold stress, maintaining the stability of the cell membrane. Sixteen R2R3-MYB TFs genes were identified from the tea plant genome database. Quantitative RT-PCR analysis showed that three CsMYB genes were strongly induced under a combination of MeJA and cold-stress treatment. Subcellular localization assays suggest CsMYB45, CsMYB46, and CsMYB105 localized in the nucleus. Exogenous MeJA treatment enhanced the overexpression of CsMYB45, CsMYB46, and CsMYB105 in E. coli and improved the growth and survival rates of recombinant cells compared to an empty vector under cold stress. Yeast two-hybrid and bimolecular fluorescence complementation experiments confirmed that CsMYB46 and CsMYB105 interacted with CsJAZ3, CsJAZ10, and CsJAZ11 in the nucleus. Taken together, these results highlight that CsMYB45, CsMYB46, and CsMYB105 are not only key components in the cold-stress signal response pathway but also may serve as points of confluence for cold stress and JA signaling pathways. Furthermore, our findings provide new insight into how MYB TFs influence cold tolerance via the jasmonic acid pathway in tea and provide candidate genes for future functional studies and breeding.